2014
DOI: 10.3389/fpsyg.2014.00918
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a novel environment improves motivation and promotes recall of words

Abstract: Active exploration of novel environments is known to increase plasticity in animals, promoting long-term potentiation in the hippocampus and enhancing memory formation. These effects can occur during as well as after exploration. In humans novelty’s effects on memory have been investigated with other methods, but never in an active exploration paradigm. We therefore investigated whether active spatial exploration of a novel compared to a previously familiarized virtual environment promotes performance on an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 60 publications
6
68
2
Order By: Relevance
“…For example, Fenker et al (2008) showed a series of either novel or familiar images a few minutes before learning, and found that the novel images yielded better learning. This finding was recently replicated using virtual reality environments: Exploring a novel environment resulting in better encoding of words a few minutes after exploration ended, relative to exploring a familiar environment (Schomaker, van Bronkhorst & Meeter, 2015). Both findings are consistent with reports that exploring a novel environment results in the release of acetylcholine on the scale of minutes (Giovannini et al, 2001), and with studies showing dopaminergic effects on plasticity lasting minutes (Li, Cullen, Anwyl, & Rowan, 2003).…”
Section: Is Novelty Beneficial For Memory?supporting
confidence: 75%
“…For example, Fenker et al (2008) showed a series of either novel or familiar images a few minutes before learning, and found that the novel images yielded better learning. This finding was recently replicated using virtual reality environments: Exploring a novel environment resulting in better encoding of words a few minutes after exploration ended, relative to exploring a familiar environment (Schomaker, van Bronkhorst & Meeter, 2015). Both findings are consistent with reports that exploring a novel environment results in the release of acetylcholine on the scale of minutes (Giovannini et al, 2001), and with studies showing dopaminergic effects on plasticity lasting minutes (Li, Cullen, Anwyl, & Rowan, 2003).…”
Section: Is Novelty Beneficial For Memory?supporting
confidence: 75%
“…A first animal demonstration showed that novelty exploration indeed can facilitate consolidation in subsequent declarative memory formation and lead to improved recall 24 h later (Salvetti et al, 2014). Similar effects of novelty exploration in humans, have so far been reported for immediate memory tests (Fenker et al, 2008;Schomaker et al, 2014). Also in this domain, there is preliminary evidence that transfer in training of some skills may depend on individual differences in prefrontal dopamine availability.…”
Section: Resultsmentioning
confidence: 72%
“…These paradigms generally expose participants to novelty, then have them study new information. Such paradigms have been shown to improve subsequent memory for information learnt after an exposure to novelty compared with performance after exposure to familiar information (e.g., Fenker et al, 2008;Schomaker et al, 2014).…”
Section: Novelty System Activationmentioning
confidence: 99%